Optical follow-up study of 32 high-redshift galaxy cluster candidates from Planck with the William Herschel Telescope. Issue 2 (5th July 2019) - Zohren, Hannah; Schrabback, Tim; van der Burg, Remco F J; Arnaud, Monique; Melin, Jean-Baptiste; van den Busch, Jan Luca; Hoekstra, Henk; Klein, Matthias
Abstract: The Planck satellite has detected cluster candidates via the Sunyaev Zel'dovich (SZ) effect, but the optical follow-up required to confirm these candidates is still incomplete, especially at high redshifts and for SZ detections at low significance. In this work, we present our analysis of optical observations obtained for 32 Planck cluster candidates using ACAM on the 4.2-m William Herschel Telescope. These cluster candidates were pre-selected using SDSS, WISE, and Pan-STARRS images to likely represent distant clusters at redshifts z ≳ 0.7. We obtain photometric redshift and richness estimates for all of the cluster candidates from a red-sequence analysis of r -, i -, and z -band imaging data. In addition, long-slit observations allow us to measure the redshifts of a subset of the clusters spectroscopically. The optical richness is often lower than expected from the inferred SZ mass when compared to scaling relations previously calibrated at low redshifts. This likely indicates the impact of Eddington bias and projection effects or noise-induced detections, especially at low-SZ significance. Thus, optical follow-up not only provides redshift measurements, but also an important independent verification method. We find that 18 (7) of the candidates at redshifts z > 0.5 ( z > 0.8) are at least half as rich as expected from scaling relations, thereby clearly confirming these candidates as massive clusters. While the complex selection function of our sample due to our pre-selection hampers its use for cosmological studies, we do provide a validation of massive high-redshift clusters particularly suitable for further astrophysical investigations.